Nursing Care in Tn. N And Tn. R with Problems of Sensory Perception Disorders: Hearing Hallucinations - Muntiara, Indah; Apriliza, Adelia (International Journal Scientific and Professional, 2023)
Hallucinations are the client's perception of the environment without any real stimulus, which means the client interprets something real without external stimulus. The purpose of this writing is to describe the nursing management of sensory perception disorders: auditory hallucinations in Mr. N and Mr. R at RSJ Palembang. The method used is to provide management in the form of patient care to control the auditory hallucinations they experience. Patient management was carried out for 5 days for Mr. N and Mr. R. Data collection techniques were carried out using interview techniques, physical examination and observation. Management results showed that clients were able to control the auditory hallucinations they experienced, namely by shouting, having conversations, scheduled activities and taking medication. Clients are able to overcome the hallucinations they experience as a whole so that the treatment given can provide optimal results. Suggestions for RSJ are expected to improve nursing care for sensory perception disorders: hallucinations by involving clients in various activities in the room so that clients remain focused and do not get lost in their hallucinations